(3GdGSJPcGQ dePGgH YdeGA GdCeUGQ ajeG JVefg GdehWC ef eYGfj GdQCj hGdBKGQs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3cJGH GdCTQHg HGH GdMO ai GdNeQ s
(3BNQgG (B:s
(3HGH CSeGA GdfHi Udi Gddg Ydjg hSde hgh BNQ GdcJGH s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(1481(3c(B) s
Keywords: (3Gdabg GdeGdcjs